Determination of Polyetheretherketone (PEEK) mechanical properties as a denture material - Saja A. Muhsin; Paul V. Hatton; Anthony Johnson; Nuno Sereno; Duncan J. Wood (Saudi Dental Journal)
Purpose: To optimize the gypsum mold temperatures for pressed PEEK, and to estimate the impact, tensile strength and flexural properties of pressed and milled PEEK. Where appropriate, these properties were compared with those of PMMA. Materials and Methods: Since the mold temperature could affect the properties of the injected parts, the temperature of 20 gypsum specimens was monitored using the multi-thermocouple system (n = 5). A total of 210 specimens were prepared for mechanical tests according to the ISO standard for denture base polymer (n = 10). The Izod impact, tensile strength, and flexural behavior were assessed. PEEK-OptimaNI1 (PEEK-pressed) was tested after processing via the pressing method at4 different mold temperatures. Machining PEEK-Juvora (PEEK-milled) specimens were prepared using the CAD-CAM production method. Data were analyzed via one-way ANOVA performed at a confidence level of 95% and a significant P-value of (P ≤ 0.05). Results: In comparison to the furnace temperature more heat was required to preheat the gypsum mold up to 100, 150, 175 and 200 °C for pressing purposes. The highest impact strength was 5.7 kJ/m2 for PEEK-pressed at 100 °C mold temperature and 4 kJ/m2 for PEEK-milled. The latter had a higher tensile strength of 118 MPa. The best result for PEEK-pressed was 97 MPa at 200 °C mold temperature. Under a 4-point bending test, Young’s modulus of PEEK-milled was 5591 MPa, while the highest for PEEK-pressed was 4936 MPa at 200 °C mold temperature. Conclusions: Compared to PMMA, given the superior mechanical properties of PEEK, it may become the material of choice for future use. Dentures constructed from PEEK polymer could well be routinely constructed in the near future. Keywords: Polyetheretherketone, Denture base material, Impact strength, 4-point bend, Tensile strength, Mold temperature, Injection molding, CAD-CAM